Analysis Of Student Learning Difficulties In Digital Literacy-Based Learning On Social Arithmetic Material - Utari, Yuli Putri; Panglipur, Indah Rahayu; Anas, Aswar (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
This study aims to analyze and find out the Analysis of Student Learning Difficulties in Digital Literacy-Based Learning on Social Arithmetic Material. The problems in this study are how student learning difficulties in digital literacy-based learning in Social Arithmetic material and what factors influence student learning difficulties in digital literacy-based learning in Social Arithmetic material. The research method used is descriptive qualitative. Data collection techniques in this study through observation, interviews, tests and documentation. The level of student learning difficulties in digital literacy-based learning on social arithmetic material at SMP Negeri 2 Sukowono is in the high category, namely 27 students with a percentage of 50%.